Preocupação com a privacidade na internet : uma pesquisa exploratória no cenário brasileiro - Silva, Vergilio Ricardo Britto da (2015)
The Internet Privacy Concern - IPC is a study area that is receiving more attention nowadays due to the extensive amount of personal information being transferred through the Internet. The constant scandals of privacy invasion and espionage involving heads of state have brought more evidence for this discussion. This research addresses the topic Information Security, focusing on Internet Privacy Concern. The growth of Information and Communication Technologies usage has generated challenges for fundamental rights, namely: the right to privacy, freedom of expression and freedom of association. The large amount of personal information that is daily published on the Internet endanger those rights. Ensuring privacy on the Internet does not depend on exclusively protection technologies, but mainly of user awareness about the importance of understanding the risks they are exposing themselves and knowing the consequences of these risks. The aim of this research was to identify the degree of concern about the privacy among Internet users in Brazil, related to Data Collection, Secondary Use, Errors, Improper access, Control over The Information, Awareness, Trust and Risk, and to identify which piece of information users notice as more sensitive in relation to privacy. This research is based on theoretical studies on Privacy on the Internet, Privacy Concern and User Behavior, showing the evolution of Concern construct wi th the Privacy and indicate how users deal with their privacy. The data collection instrument employed in this study originated in the study of Smith et al. (1996), and has been improved by several studies up to the final version of Hong and Thong (2013). A descriptive exploratory survey was conducted aiming to identify opinions that are being manifested in the target population of this study, which are Internet users in Brazil that according to the IBGE survey (2013), totaled 77,7 million users. Data were collected in the five regions of the country, summing up 1,104 completed questionnaires. The results indicate a high degree of concern for the privacy of Internet users in Brazil, mainly in the South and South-East regions, which showed the highest concernment indexes. Among the information identified as sensitive are, in order of greatest concern, passwords, credit card number, checking account number and agency, bank balance, spending on credit card and overdraft limit. Among the less sensitive informa tion is sexual orientation, addictions, school where they have studied, date of birth and school grades.